Application of gene editing technology in cattle genetic breeding - Yanan Xu; Lishuang Song; Zhuying Wei; Guangpeng Li; Lei Yang (Agriculture Communications, 2025)
Gene editing technology is a groundbreaking biotechnology tool that presents significant opportunities and challenges in livestock breeding. It enables precise genome modification by efficiently and accurately inserting, deleting, or substituting DNA sequences. These modifications can alter phenotypic traits, thereby accelerating the breeding process. Notable progress has been made in enhancing key economically important traits in cattle, including disease resistance, meat quality, lactation performance, and sex control. This review summarizes research progress on gene editing technology in cattle genetic breeding and analyzes challenges and future directions for its development.